β-Catenin gain of function in muscles impairs neuromuscular junction formation - Wu, Haitao (Company of Biologists, 2012)
Neuromuscular junction (NMJ) formation requires proper interaction between motoneurons and muscle cells. β-Catenin is required in muscle cells for NMJ formation. To understand underlying mechanisms, we investigated the effect of β-catenin gain of function (GOF) on NMJ development. In HSA-β-cat(flox(ex3)/+) mice, which express stable β-catenin specifically in muscles, motor nerve terminals became extensively defasciculated and arborized. Ectopic muscles were observed in the diaphragm and were innervated by ectopic phrenic nerve branches. Moreover, extensive outgrowth and branching of spinal axons were evident in the GOF mice. These results indicate that increased β-catenin in muscles alters presynaptic differentiation. Postsynaptically, AChR clusters in HSA-β-cat(flox(ex3)/+) diaphragms were distributed in a wider region, suggesting that muscle β-catenin GOF disrupted the signal that restricts AChR clustering to the middle region of muscle fibers. Expression of stable β-catenin in motoneurons, however, had no effect on NMJ formation. These observations provide additional genetic evidence that pre- and postsynaptic development of the NMJ requires an intricate balance of β-catenin activity in muscles.